Rancang Bangun Sistem Informasi Akuntansi Pengelolaan Cash Advance Purchasing Project PT. Akashi Wahana Indonesia Karawang - Komalasari, Yuli; Monika, Sintia (Sistem Informasi Akuntansi Kampu Kabupaten Karawang, 2023)
The development of time information technology is very helpful in every activity such as in work activities in offices, it is very helpful for employees in managing the dissemination of work-related information. PT Akashi Wahana Indonesia supports technological advances based on the 2020 AOP Group Message with the theme: